The Role Of Guidance Counseling Teachers in the Independent Curriculum Towards Forming the Profile Of Pancasila Students - Rizki Kurniawan; Firman; Mohd. Suhadi Bin Mohamed Sidik (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2025)
The Ministry of Education and Culture of the Republic of Indonesia has established a strategic plan to encourage the progress of students who adhere to the principles of Pancasila. This approach requires the participation of various stakeholders at both broader and specific levels, including educational counselors who have an important function in achieving this goal. This essay explores the role of counselors in forming Pancasila student profiles and the subsequent influence on students' personal resilience, by utilizing literature study techniques. School counselors have the task of developing character education by cultivating personal resilience attributes in students, such as self-confidence, commitment to principles, autonomy, and accountability. This is in line with the six character profiles of Pancasila students, which include religious faith, firm commitment to God, and virtuous ethics; embracing global diversity; foster collaboration; promote independence; encourage critical thinking; and foster creativity. In addition, it is very important to foster collaboration between all parties involved in order to actively anticipate and overcome the impacts that may arise from the application of counterproductive methods in the field of counseling.